Roles of intestinal intraepithelial lymphocytes in specific-pathogen-free chickens infected with lentogenic and velogenic newcastle disease virus strains - Hamisu, Tasiu Mallam (2021)
There are increasing reports of Newcastle disease virus (NDV) shedding in vaccinated poultry flocks. Two intraepithelial lymphocytes (IEL), the Natural Killer (NK) cells and T cells, play a critical role in the control of virus shedding. The main objective of this study is to investigate the role of these cells in specific-pathogen-free (SPF) chickens following inoculation with NDV lentogenic strain LaSota, and/or velogenic strains, genotypes VII and VIII. The SPF chickens were divided into groups of inoculated with lentogenic strain (LaSota); genotype VII (GVII); genotype VIII (GVIII); lentogenic and challenged with genotype VII (LSGVII); lentogenic and challenged with genotype VIII (LSGVIII); and the group of uninfected control. Immunophenotyping of NK and T cells subtypes was conducted using a flow cytometry. Furthermore, CD3-/CD25+/CD45+IEL NK cell was purified, and the expression profile of immune and apoptosis-related genes was quantified using Reverse Transcriptase Quantitative Polymerase Chain Reaction (RTqPCR). Virus shedding was then measured using RT-qPCR. Data were analysed using Two-way Analysis of Variance (ANOVA). The percentage of CD3+ cells showed a decreasing pattern in GVII and GVIII challenged groups compared with LSGVII and LSGVIII. Similarly, a steady decrease of CD3+/CD4+ cells in GVII and GVIII challenged groups was seen as the infection progressed. LSGVII and LSGVIII challenged groups, however, showed a statistically significant increase of these cells. A similar finding was obtained with CD3+/CD8+ cells. Among all the experimental groups, the highest virus shedding occurred at 60 hrs postchallenge with GVII. There was a strong negative correlation between an increase in GVII shedding and a decrease in CD25+IEL NK cells. Following inoculation of LGVII, there was a statistically significant decrease in virus shedding in all the time points; however, there was no significant correlation between GVII shedding and CD25+IEL NK cells. There was no statistically significant difference in GVIII shedding between the time points of the GVIII challenge group and its corresponding LSGVIII group. There was a strong positive correlation between CD25+IEL NK cells and GVIII shedding in a LSGVIII challenged group. The expression profiles of CD69, FasL and granzyme A, NK-lysin, and IFN-γ were generally upregulated in LSGVII and LSGVIII challenged groups. In contrast, B-NK, was downregulated. In NDV GVII and GVIII challenged groups, however, B-NK was upregulated, whereas the remaining receptors were generally downregulated except for CHIR- AB1. Taking together, the findings of this study showed that CD25+IEL NK cell showed a strong negative correlation with GVII shedding, but no correlation with GVIII shedding. Furthermore, there was a moderate negative correlation between CD25+IEL NK cells and GVII shedding in LSGVII challenge group and a strong positive correlation between CD25+IEL NK and GVIII shedding in LSGVIII challenged chickens. The CD3- /CD25+/CD45+IEL NK cells in the LSGVII and LSGVIII showed enhanced NK cell activity through upregulation of the activating receptors, peptides and interferon-γ. In contrast, the function of CD3-/CD25+/CD45+IEL NK was downgraded through upregulation of inhibitory receptors following inoculation of GVII and GVIII NDV. In addition, enriched CD3-/CD25+/CD45+IEL NK cells may use both receptor and granules-mediated apoptosis pathways in killing virus-infected cells.